THE INFLUENCE OF HIGHER ORDER THINKING SKILLS (HOTS) AND CLASS MANAGEMENT ON STUDENT LEARNING OUTCOMES AT TONDANO 2 STATE HIGH SCHOOL - Sjeddie Rianne Watung; Listriyanti Palangda (J-Shelves of Indragiri (JSI), 2023)
Learning outcomes are a student's abilities obtained after learning activities, including cognitive, affective and psychomotor abilities. Learning outcomes are influenced by many factors including higher order thinking abilities (HOTS) and classroom management. The aims of this research are: 1) To determine the effect of HOTS on student learning outcomes at SMA 2 Tondano; 2) To determine the effect of classroom management on student learning outcomes at SMA 2 Tondano; 3) To determine the effect of HOTS and classroom management on student learning outcomes at SMA 2 Tondano. This research is quantitative research with a total research sample of 115 people. The data analysis techniques used are regression and correlation. The research results show that; 1) There is an influence of HOTS on student learning outcomes at SMA 2 Tondano of 69%; 2) There is an influence of class management on student learning outcomes at SMA 2 Tondano by 16%; 3) There is an influence of HOTS and class management on student learning outcomes at SMA 2 Tondano by 69%.